Cross-Sectional Analysis of Pituitary Gland Zones Exposed to Thyroid Modulators - Asma Khuwaja; Shahida Hingoro; Shuja Kazi; Munir Ahmed Channa; Muhammad Khaliq (Pakistan Journal of Medicine and Dentistry)
Background: The pituitary gland takes part in coordinating the hypothalamic-pituitary-thyroid (HPT) network. This study aimed to examine the effects of hypothyroidism and hyperthyroidism on the structure of the pars distalis, pars intermedia, and pars nervosa regions of the pituitary gland.